The effects of communication mode on negotiation of meaning and its noticing. Issue 3 (3rd March 2014) - Yuksel, Dogan; Inan, Banu
Abstract: This study examined the effects of communication mode ( i.e., face to face versus computer mediated communication) on the instances of negotiation of meaning (NofM) and its level of noticing by learners. Sixty-four participants (32 dyads) completed two jigsaw tasks in two different mediums (one in each) and four days after the tasks they were asked to identify the instances where they had communication breakdowns in a stimulated recall protocol. The findings of the study revealed that the average number of the NofM exchanges and durations of the tasks were higher in face to face mode (F2F) but the participants of the synchronous computer mediated communication (SCMC) group noticed a higher average of NofM instances ( M =10.72) compared to the F2F group ( M =9.13) and the difference was significant. Based on these results, we can argue that F2F promotes a better context for the production of NofM, but the SCMC environment leads to more instances of noticing.